2011
DOI: 10.3109/02703181.2011.625107
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Utilizing a Combination of External Visual and Auditory Cues as a Gait Training Strategy in a Pharmaceutically Untreated Patient with Parkinson's Disease: A Case Report

Abstract: One major functional problem that many individuals with Parkinson's disease (PD) face is gait difficulties, including a shuffling gait and freezing episodes. Proposed treatment options in physical therapy (PT) include teaching PD patients to utilize external cues in order to allow for a more efficient gait. The purpose of this case study was to compare the effectiveness of visual cue alone and combined visual and auditory cues on various gait parameters in a patient with PD, who was not receiving pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…For example, we hope to get Patrick to step on the balance test to a slow rhythm initially and this may enable him to more effectively hold his balance and/or make more balanced steps. Auditory rhythmic Parkinson's disease (Dvorsky, Elgelid & Chau, 2011). Such programmes offer benefits both as an effective diagnostic tool and a form of treatment for such conditions.…”
Section: Task 2 Balance-'y' Balance Exercise With Visual Feedbackmentioning
confidence: 99%
“…For example, we hope to get Patrick to step on the balance test to a slow rhythm initially and this may enable him to more effectively hold his balance and/or make more balanced steps. Auditory rhythmic Parkinson's disease (Dvorsky, Elgelid & Chau, 2011). Such programmes offer benefits both as an effective diagnostic tool and a form of treatment for such conditions.…”
Section: Task 2 Balance-'y' Balance Exercise With Visual Feedbackmentioning
confidence: 99%
“…Practice= Over the course of the ten weeks Patrick will observe the teacher and himself performing the tasks on a weekly basis. Parkinson's disease (Dvorsky, Elgelid & Chau, 2011). Such programmes offer benefits both as an effective diagnostic tool and a form of treatment for such conditions.…”
Section: Task 2 Balance-'y' Balance Exercise With Visual Feedbackmentioning
confidence: 99%
“…Many studies suggest that auditory [11][12][13][14] and visual cues [13][14][15][16][17][18][19][20][21][22][23][24][25][26] can improve a PwP's gait performance, especially during FOG. Rubinstein et al [14], observed that in the presence of an external "movement trigger" (i.e., a sensory cue), a patient's selfpaced actions such as walking, can be significantly improved; a phenomenon, known as "kinesia paradoxica".…”
Section: Introductionmentioning
confidence: 99%